ANALISIS SIKAP PEDULI LINGKUNGAN SISWA SD NEGERI 184 PEKANBARU - Hadi Gunawan; Guslinda (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
The background of this research is the importance of instilling an attitude of environmental care from an early age, starting at the elementary school level. The purpose of this study was to determine the level of students’ environmental care attitude at SD Negeri 184 Pekanbaru. This study employed a descriptive quantitative research design. The research was conducted at SD Negeri 184 Pekanbaru. Based on the research results assessed through six indicators, namely cleaning toilets, cleaning trash bins, maintaining the school environment, beautifying classrooms and school areas with plants, participating in maintaining school parks, and participating in maintaining environmental cleanliness. The findings showed that students of SD Negeri 184 Pekanbaru demonstrated a very high level of environmental care attitude, with an acquisition score of 89.02, which falls into the very caring category.